Exosomal MicroRNA-181a Derived From Mesenchymal Stem Cells Improves Gut Microbiota Composition, Barrier Function, and Inflammatory Status in an Experimental Colitis Model - Gu, Li; Ren, Feng; Fang, Xianrui; Yuan, Lianwen; Liu, Ganglei; Wang, Shalong (Frontiers in Medicine, 2021)
Background: Mesenchymal stem cell (MSC)-derived exosomes (Exos) are recently proved to be a promising candidate for ulcerative colitis (UC), but the mechanism remains unclear. We herein investigated the effects of MSC-derived Exosomal microRNA-181a (miR-181a) on gut microbiota, immune responses, and intestinal barrier function in UC. Methods: Human bone marrow MSC-derived exosomes were extracted and identified via transmission electron microscopy (TEM), Nanoparticle Tracking Analysis (NTA) and Western blotting. Dextran sodium sulfate (DSS)-induced colitis model and lipopolysaccharide (LPS)-induced human colonic epithelial cells (HCOEPIC) model were established to determine the effect of MSC-Exos on intestinal barrier function, immune responses, and intestinal barrier function in vivo and in vitro. The relationship between miR-181a and UC was analyzed using the GEO database. MSC-miR-181-inhibitor was used to reveal the role of exosomal miR-181a in DSS-induced colitis. Results: TEM and NTA results showed that Exos of a diameter of about 100 nm with the round and oval vesicle-like structure were successfully extracted. The expressions of the CD63, CD81, and TSG101 proteins were positive in these Exos. After MSC-Exos treatment, the colon length in colitis mice increased; colon inflammatory injury decreased; TNF-α, IL-6, IL-1β, IL-17, and IL-18 levels decreased; and Claudin-1, ZO-1, and IκB levels increased. In addition, the structure of the gut microbiota in DSS-induced colitis mice was changed by MSC-Exos. MSC-Exos showed anti-apoptotic effects on LPS-induced HCOEPIC. The protective effects decreased significantly by treatment with MSC-Exos interfered with miR-181a inhibitor in vivo and in vitro. Conclusion: MSC-derived Exosomal miR-181a can alleviate experimental colitis by promoted intestinal barrier function. It exerted anti-inflammatory function and affected the gut microbiota. This indicates that MSC exosomal miR-181a may exhibit potential as a disease-modifying drug for UC.